Synthesis of arbitrary current mode filter - LI Zhi-jun1; WANG Chun-hua2; LIU Rong1 (Tongxin xuebao)
A new general analytical synthesis method for arbitrary current mode filter was presented.The method was based on the analytical decomposition of a complicated high-order transfer function into n lossless integrators and n cur-rent proportional blocks by a succession of innovative algebra process.The filter structure based on MCCIIs was pro-posed with the following advantages: 1) it can be used not only for arbitrary-order filters,but also for different filter types such as Butterworth,Chebyshev and Elliptic;2) the circuit structure proposed only contains（2n+1） active elements,（2n+1） resistors and n capacitors;3) all the elements are grounded,so it is convenient to be integrated;4) the different filter functions such as high-pass,low-pass,band-pass,band-reject and all-pass can be obtained when it act as a Butter-worth filter.A third-order elliptic low-pass filter and a sixth-order Butterworth universal filter were employed to demon-strate the realization scheme.The validity of the proposed structure was verified through PSPICE simulations.